Investigations on the frequency and temperature effects on mechanical properties of a shape memory polymer (Veriflex). (August 2015) - Butaud, P.; Placet, V.; Klesa, J.; Ouisse, M.; Foltête, E.; Gabrion, X.
Highlights: Validation of the time temperature superposition for a shape memory polymer. Combination of DMA, modal and static tests for wideband characterization of a SMP. Discussion on the time–temperature superposition based on the WLF and Arrhenius law. Abstract: This study proposes a comparison between three identification methods of the mechanical properties of a shape memory polymer (Veriflex®): quasi-static tensile tests, tensile dynamic mechanical analysis (DMA) and modal tests. The Young's modulus and the Poisson's ratio are determined at ambient temperature using the first technique. The DMA is used to determine the evolution of the viscoelastic properties versus the temperature and the frequency under harmonic loading. The modal analysis is used to identify the viscoelastic properties of the material at higher frequencies. The purpose of this study is to check the validity of the time–temperature equivalence for the Veriflex® obtained from the DMA measurements. It is shown that the viscoelastic properties predicted through the master curve are consistent with the measurements collected using quasi-static and modal test. The aging effect on SMP properties is also quantified.